Education and science: current trends - Murzina Z. V., Stepanova L. A., Shtykova A. V., Babaeva N. M., Belova N. G., Morozov A. P., Ledniova V. S., Moshurova L. V., Korchagina N. S., Kolomatskaia V. V., Zalunin V. I., Zhadan V. N., Solnyshkina M. G., Kuzina N. A., Tochilina I. N., Ulianova L. V., Ledneva V. S., Talykova M. I., Korchagina N. S., Kriuchkova A. V., Litvinenko N. K., Koniagina M. N., Fomenko N. V., Gorbunov P. I., Gorkinskii R. I., Milioshina N. A., Potapova L. A., Barashkina S. B. (Education and science: current trends, 2020)
the dominance of the technocratic model of civilization development has led to a number of global problems, each of which threatens the destruction of humanity. The most terrible of the threatening catastrophes is the anthropological one, the destruction of the human being in man. The necessity for comprehensive humanization of all spheres of human activity is argued. Humanitarization of higher technical education is considered the most important mechanism and means of forming a professional's humanitarian culture. The article presents the results of a study where a technical university students’ attitude to the study of Humanities was analyzed. The article reflects the problem of training teaching staff for technical universities and considers the reserves for improving the quality of training of undergraduates as prospective teachers. A three-stage model of undergraduates’ comprehensive training for professional and pedagogical activities of a technical university teacher is presented.
Keywords: гуманитаризация; гуманизация; антропологический кризис; humanization; высшее техническое образование; higher technical education; гуманистическая культура профессионала; подготовка магистрантов к научно-педагогической деятельности; модель комплексной подготовки магистрантов; anthropological crisis; humanitarization; humanistic culture of a professional; preparation of undergraduates for scientific and pedagogical activity; model of complex preparation of undergraduates